POR QUE OS BRASILEIROS NÃO CONFIAM NOS PARTIDOS? BASES PARA COMPREENDER A CULTURA POLÍTICA (ANTI)PARTIDÁRIA E POSSÍVEIS SAÍDAS - Marcello Baquero; Bianca de Freitas Linhares (Revista Debates, 2011)
Political parties are considered the most important institutions of political mediation between the State and society. Thus the role of political representation is an essential component of strengthening democratic political values and political institutions. However, despite significant formal democratic advances, Brazil continues to face obstacles that could undermine those advances. In this article, we seek to understand why Brazilians don’t trust political parties. The data utilized are from probabilistic opinion surveys conducted nationally and at the level of State and from a historicalretrospective. We end the article analyzing the benefits that could result from a combination of formal political representation mechanisms and alternative societary forms of political involvement.